Severity of developmental delay and parenting behavior in toddlers with neurodevelopmental disabilities - Castagna, Annalisa; Butti, Niccolò; Cordolcini, Laura; Innocenti, Mark S.; Montirosso, Rosario (Frontiers in Psychology, 2024)
Introduction The presence of a neurodevelopmental disability (ND) represents an adverse condition for child’s development and parent–child relationship, and it is reasonable to assume that the severity of delay may influence parenting behavior. Previous research, however, did not specifically address this issue. Methods This cross-sectional study compared parental behaviors of mothers of toddlers with moderate/severe or mild/borderline developmental delay and mothers of toddlers with typical development, while considering maternal emotional states. A total of 88 dyads with children aged between 12 and 47 months participated in a 10-min video-recorded interaction then coded with the PICCOLO, a validated observation checklist that assesses four dimensions of parenting: affection, responsiveness, encouragement, and teaching. The mothers also fulfilled two standardized questionnaires assessing parental stress and presence of depressive symptoms. MANOVA and MANCOVA models were used to explore between-group differences in specific parenting dimensions, also considering parental stress. Results Mothers of toddlers with ND were less responsive than the comparison group, while the presence of a moderate/severe developmental delay specifically affected teaching behaviors. No differences emerged for affection and encouragement behaviors. Importantly, although mothers of toddlers with moderate/severe ND reported higher child-related dysfunctional interaction stress, this did not directly affect parenting behaviors. Discussion These findings highlight how the presence of a disability and the severity of developmental delay can affect specific dimensions of parenting (i.e., responsiveness, teaching) and might inform clinical practice and research on early parental interventions.